UNJUK KERJA PEMBANGKIT LISTRIK TENAGA SURYA ROOFTOP 158 KWP PADA KANTOR GUBERNUR BALI - M.R. Wicaksana; I.N.S. Kumara; I.A.D Giriantari (Jurnal SPEKTRUM, 2019)
The Provincial Government of Bali is collaborating with the Ministry of Energy and Mineral Resources for the developing a 158 kWp rooftop solar power plant that connected to the grid of PLN. The energy produced so far has reduced the supply of electricity from PLN in the Bali Governor's Office area. The purpose of research studies is know the potential energy produced by solar power plant 158 kWp. Energy production is estimated using HelioScope simulation. Data needed includes location of the solar power plant, and solar power plant technical specifications. The simulation produces total energy data in a year of 249,764 kWh/year with the highest energy occurring in May of 24,172 kWh and the lowest energy occurring in January of 16,226 kWh.